The Effect of Environmental pH on Polymeric Transfection Efficiency - Kang, Han Chang (2011)
Although polymers, polyplexes, and cells are exposed to various extracellular and intracellular pH environments during polyplex preparation and polymeric transfection, the impact of environmental pH on polymeric transfection has not yet been investigated. This study aims to understand the influence of environmental pH on polymeric transfection by modulating the pH of the transfection medium or the culture medium. Changes in the extracellular pH affected polymeric transfection by way of complex factors such as pH-induced changes in polymer characteristics (e.g., proton buffering capacity and ionization), polyplex characteristics (e.g., size, surface charge, and decomplexation), and cellular characteristics (e.g., cellular uptake, cell cycle phases, and intracellular pH environment). Notably, acidic medium delayed endocytosis, endosomal acidification, cytosolic release, and decomplexation of polyplexes, thereby negatively affecting gene expression. However, acidic medium inhibited mitosis and reduced dilution of gene expression, resulting in increased transfection efficiency. Compared to pH 7.4 medium, acidic transfection medium reduced gene expression 1.6~7.7-fold whereas acidic culture medium enhanced transfection efficiency 2.1~2.6-fold. Polymeric transfection was affected more by the culture medium than by the transfection medium. Understanding the effects of extracellular pH during polymeric transfection may stimulate new strategies for determining effective and safe polymeric gene carriers.